The Role of Local Wisdom in Driving Innovation and Green Economic Growth through Digital Platforms - Oktaviani, Intan; Widyaningsih, Pipin; Triana; Husin, Husna Sarirah (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
This study investigates the transformative potential of integrating local wisdom encompassing indigenous knowledge, cultural values, and traditional ecological practices into digital platforms to drive innovation and foster green economic growth, aligning with global sustainability agendas. It highlights how local wisdom, often manifested in heritage crafts, regenerative agriculture, and community-based resource management, serves as a foundation for eco-friendly production systems, ethical trade, and inclusive entrepreneurship when amplified through digital technologies such as e-commerce, traceability systems, and financial technology. Employing a mixed-method approach involving case studies from Asia, Africa, and Latin America alongside quantitative analyses of export growth, job creation, and supply chain resilience, the research reveals that embedding cultural identity and sustainable practices into digital commerce enhances product authenticity, attracts premium markets, reduces carbon footprints through localized production, and empowers marginalized groups, including women and indigenous communities. The findings underscore that such integration not only contributes to fair trade and decent work but also strengthens biodiversity conservation, promotes circular economy principles, and mitigates socio-economic inequalities. The study recommends implementing policy incentives, digital literacy programs, and multi-stakeholder collaborations between governments, platform developers, and cultural institutions to scale these initiatives, ultimately positioning local wisdom as a strategic driver for environmentally responsible, socially inclusive, and innovation-driven economic transformation in the digital era.